Opportunistic Related Party Transactions Practices: A Comparative Study on Different Ownership Structures in Indonesia's Energy Sector - Wiwin Theresia Sitinjak; Nureni Wijayati (Eduvest - Journal of Universal Studies, 2026)
This study examines opportunistic behavior in Related Party Transactions (RPT) across six Indonesian energy companies with varying ownership structures (state-owned, family- owned, and foreign-owned) during 2019–2023. The research employs an evaluative case study approach combined with thematic content analysis supported by NVivo. The results reveal substantial variation in tunneling and propping patterns across ownership types. Highly concentrated family-owned firms exhibit aggressive tunneling through extreme dividend extraction of 49–76% during the windfall profit period (2022–2023), while state- owned enterprises demonstrate minimal tunneling (1–2.3 on a 0–21 scale) and strong propping during financial distress (2020–2021). These patterns are elastic to external shocks, as reflected in tunneling–propping ratio shifts from 70:30 (pre-pandemic 2019), 46:54 (pandemic 2020–2021), to 84:16 (commodity boom 2022–2023). Internal factor analysis identifies ownership concentration as the primary driver of opportunistic behavior; however, its impact varies depending on ownership type and external enforcement strength. Formal governance mechanisms including Big-4 audits, 86% board independence, and compliance with POJK 42/2020 are insufficient to curb tunneling when controlling shareholders are dominant, whereas government oversight in state-owned enterprises proves more effective than internal governance mechanisms. The findings suggest that regulatory remedies must address the underlying control–ownership divergence, with recommendations including strengthened fairness opinion standards, enhanced monitoring during windfall periods, and codified dividend policy constraints for state-owned energy companies.